Developing, validating and evaluating the effectiveness of a blended learning for teaching clinical surgical nursing skills among nursing students at Xiangnan University in Chenzhou, China - Afang, Li (2025)
Online teaching is a new teaching method, and there is not much research on teaching clinical nursing skills and even less on the online teaching of this aspect of nursing apprenticeships. This study aimed to develop, validate, and evaluate a surgical nursing apprenticeship online and offline blended teaching module using the Learning Pass mobile app. This quantitative study design was carried out in two phases. Phase I involved the development and validation of a surgical nursing apprenticeship online and offline blended teaching module using the Learning Pass mobile app. The researchers and teaching team developed a blended teaching module based on the syllabus and literature review. After that, the blended teaching module was validated by ten experts using the Delphi method. In Phase II, a randomized control trial was conducted among 166 nursing students at Xiangnan University in Chenzhou, China, to evaluate the effectiveness of the blended teaching module towards skill performance, self-directed learning ability, online academic emotions, and learning attitude. The intervention group utilized online and offline blended teaching methods using the Learning Pass mobile app, while the control group used traditional face-to-face teaching methods. SPSS 26.0 statistical software was used for data analysis. One-sample t-tests, independent t-tests, and chi-square tests were performed. As a result of Phase I, the online and offline blended teaching module for the surgical nursing apprenticeship was agreed upon with 100% experts through two rounds of the Delphi technique. Phase II results showed that after the intervention, there was a significant increase in self-directed learning ability in the intervention group compared to the control group (p = 0.019), with the mean score for the intervention group 78.89 (SD = 13.32) and the control group 74.48 (SD = 11.55). The skill scores also showed a significant increase in the intervention group compared to the control group (p < 0.001), with the mean score for the intervention group 91.81 (SD = 3.54) and the control group 89.65 (SD = 4.11). The intervention group's mean value of online academic emotions (Mean = 3.33) was higher than the theoretical mean (Mean = 3), and the difference was statistically significant (p < 0.001). Besides that, there were no significant differences in the students' learning attitudes. In conclusion, online and offline blended teaching method using the Learning Pass mobile app effectively improves nursing skills, self-directed learning ability, and online academic emotions among nursing students. In the future, multicenter studies are needed to validate the effectiveness of this mobile app for online teaching, as well as longitudinal studies to assess long-term outcomes.